Influência de diferentes resinas compostas e técnicas de polimento sobre os tecidos periodontais próximos a lesões cervicais não cariosas avaliação clínica randomizada - Teixeira, Nancielli (2015)
The aim of this study was to evaluate the influence of different composite resins and technical polishing and finishing over periodontals tissues and gingival crevicular fluid in cervical lesions restorations noncarious (LCNC). Initially were evaluated 272 teeths of patients with complaints related to LCNC and, acordding to the inclusion and exclusion criteria were selected 60 teeths for elegibility. Each tooth received a restoration with a kind of composite resin (Resin Tetric N-Ceram® or Resin Z350 XT®) in both quadrants, varying the polishing technique ( Astropol® Polishing rubber or Sof-lex® Disks). Periodontal tissues analysis, the longitudinal evaluation of restaurations and the gengival crevicular fluid collect were taken prior to scalling and root planning and also at 30, 60, 120 and 180 days of restaurations making. After the data collection and tabulation , these were submited to the Friedman test, with a significance level of 5%. The results revealed that resins and polishing techniques applied in this study showed no estatistical differences at the end of follow-up in any of the analyzes. However all groups evaluated showed differences between the initial and final times (p <0.05). From the results obtained it was concluded that regardless of the restorative material or polishing technique, the restoration of LCNC cavities improved the periodontal health of patients